Penerapan peta konsep sebagai strategi asesmen formatif dalam upaya meningkatkan hasil belajar siswa pada pembelajaran sistem koordinasi - Ninda Eka Ratanasabilla; Siti Sriyati; Yanti Hamdiyati (Assimilation: Indonesian Journal of Biology Education, 2021)
This study aimed to examine the application of concept maps as a formative assessment strategy in an effort to improve student learning outcomes in learning coordination systems. The method in this research is pre-experimental involved only one experimental class without a control class. The research design used is one group pretest-posttest design. A total of one class of students from class XI Science in one of the high schools in Bandung has been involved as a research subject. The research instruments used include the concept map assessment rubric used by students and teachers when learning activities take place, the concept map assessment sheet to confirm the results of the concept map, and student questionnaire responses, and the pretest and posttest instruments to analyze the effect of the application of concept maps to learning outcomes in the form of mastery of student concepts. Concept map making activities are carried out individually with online learning, each student's concept map results are assessed by the teacher and then given feedback on the concept map. The results showed that there was an increase in the average value of the concept map of students after being given feedback that is equal to 64.05 to 67.91. An increase also occurred in the results of the average pretest and posttest scores after the learning activities were carried out in the amount of 40.61 to 64.39. Student responses to the application of concept maps generally showed 75.80% positive responses. The results also showed that there was an effect of the application of the concept map to student learning in the form of increasing scores in the medium category (N-gain= 0.40).